Concept Of Visha Upadrava In Ayurveda: Perspective Framework - Lamani, Preetam K (International Research Journal of Ayurveda & Yoga, 2021)
Upadrava is the complication produced in a diseased condition. As a matter of fact, this complication is also a disease with a separate entity. The only fact to be remembered is that the Upadrava develops after the formation of the main disease. The etiology of doshas remaining the same for both. Upadrava is the disease produced after the formation of the main disease and is dependent on the main disease whether the upadrava is mild or grave. Besides the above definition the following are also considered as upadrava. It is a secondary disease or complication, produced by the same dosha as is responsible for the main disease. When the main disease is produced and the doshas are further vitiated owing to the abnormal diet, behavior etc. a second disease is super added and is called upadrava. Acharya Vagbhata has stated in his classical book Ashtanga Sangraha a separate chapter about Visha Upadravas. Sushruta has talked about Visha upadrava in the context of Dushi Visha and while explaining the management of snake poisons.These Upadravas are the aggravation of symptoms as quoted besides many others as stated by Vagbhata in a person afflicted by Dushi Visha (slow poison) or Visha at a later stage which again means a form of Dushi Visha. Understanding these Upadravas in the present clinical aspect is very much appreciated. Apart from venomous bites, as a possibility we can also consider the prolonged use of contaminated substances in the form of food, air, water, land, medication etc to be akin to Visha and their ill effects as the Upadrava.